2015
DOI: 10.11606/issn.1678-4456.v52i4p310-318
|View full text |Cite
|
Sign up to set email alerts
|

Detection, quantification and genetic variability of Mycoplasma hyopneumoniae from apparently healthy and pneumonic swine

Abstract: Molecular differences among Mycoplasma hyopneumoniae strains present in pneumonic lungs of swine have been largely studied. However, no comparative studies concerning the strains present in apparently healthy pigs have been carried out. This study aimed to detect, quantify and perform molecular analysis of M. hyopneumoniae strains in pig lungs with and without pneumonic lesions. The detection of M. hyopneumoniae was performed using multiplex PCR (YAMAGUTI, 2008), real-time PCR (STRAIT et al., 2008) and multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On the other hand, some positive samples in nested-PCR did not present a lung lesion score. This result might be because of the natural process of cicatrization, whereby the microorganism remains in the respiratory tract, turning the animal into an asymptomatic pathogen carrier (Pulgarón et al, 2015;Siqueira et al, 2017). Moreover, the detection of M. hyopneumoniae in lungs without macroscopic pneumonia-like lesions may also be related to the infectious process.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some positive samples in nested-PCR did not present a lung lesion score. This result might be because of the natural process of cicatrization, whereby the microorganism remains in the respiratory tract, turning the animal into an asymptomatic pathogen carrier (Pulgarón et al, 2015;Siqueira et al, 2017). Moreover, the detection of M. hyopneumoniae in lungs without macroscopic pneumonia-like lesions may also be related to the infectious process.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained by Teixeira et al (2003) when they reported that the macroscopic lesions in the lungs were not sensitive to detect PES, since some samples that presented no macroscopic injuries to PES obtained positive results in PCR, as well as the lung samples with lesions were negative in PCR. Some samples were positive for PCR and presented no pulmonary lesions possibly due to the natural healing process, by which the microorganism remains in the respiratory tract, transforming the animal into an asymptomatic pathogen carrier (PULGARÓN et al, 2015;SIQUEIRA et al, 2017). Moreover, the detection of M. hyopneumoniae in the lungs without macroscopic lesions of the type pneumonia may also be related to the infectious process, and in these cases, the use of PCR capable of detecting small amounts of microorganisms per sample , which would be considered false negatives by less sensitive methods.…”
Section: Resultsmentioning
confidence: 99%